Achievements of international law : essays in honour of robin churchill. (London [England] : HART PUBLISHING, 2021)
"The aim of this collection of essays in Robin Churchill's honour to discuss the key examples of the achievements of international law ? with the express aim of exploring both what it has achieved and also its limits. This will serve as a response to the two popular but opposite misconceptions about the role of international law. One view is that international law is too weak to improve the World in any significant way. The other view is that international law is a panacea that can be used to rid the world of many of its ills. The book is divided into four distinct parts, each reflecting on what international law has achieved within broadly defined substantive areas. It opens with a discussion on general international law and international human rights Law, before exploring the law of the sea and fisheries. It then looks at international environmental law before finally examining the use of force and international criminal law. The chapters and the collection overall will provide a contrast to the popular misconceptions about international law by offering examples of both the success and also limitations of it as a system."--
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: International law; Electronic books